Oral and Perioral Manifestations in Monkeypox Patients: A Systematic Review of Case Reports and Case Series - Fiki Muhammad Ridho; Mohammad Iqbal; Eko Puji Laksono; Rafael Sena Saraiva Leal (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Human monkeypox (MPX) is an infectious disease caused by the MPX virus. One of the manifestations caused by MPX in humans is lesions in the oral cavity and surrounding areas. This is of particular concern, especially for dentists, when identifying MPX through oral and perioral inspection. Objective: This study aims to systematically and comprehensively describe MPX patients' oral and perioral manifestations. Methods: Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic literature search was conducted on the following databases: PubMed, ScienceDirect, Scopus, Wiley, and Google Scholar. Quality assessment was performed using the JBI critical appraisal checklist. Results: 824 articles were identified from the databases and 45 case report studies and 3 case series studies involving 57 MPX patients with oral and perioral manifestations were eligible for review. All included articles were rated moderate to high quality based on the quality assessment. According to the pooled data obtained, the most common prevalence of oral and perioral manifestations is ulcers (19.3%), followed by sore throat (18.6%), edema (10.7%), pustules (10%), erythema (7.9%), and vesicles (5.7%). Based on the location of oral and perioral lesions, the most common occurred in the oropharynx and pharynx (27.5%), perioral (17.4%), tongue (12.8%), tonsils (12.8%), and lips (10.1%). Conclusion: The most common oral and perioral manifestations in MPX patients are ulcers, sore throat, edema, pustules, erythema, and vesicles which can be found most often in the oropharynx/pharynx, perioral, tongue, tonsil and lip region.